Center-based care and parenting activities - Jonas Jessen; C. Katharina Spieß; Sevrin Waights (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We examine the relationship between parenting activities and center-based care using time diary and survey data for mothers in Germany. While mothers using center-based care spend significantly less time in the presence of their child, we find that differences in the time spent on specific activities such as reading, talking, and playing with the child are relatively small or zero. The pattern of results is more pronounced for lower education mothers. The lack of large decreases in activities are explained by two factors: (i) that center care replaces time that parents spend with the child but are doing other things such as housework or leisure (a small direct effect), and (ii) that evenings become relatively more activity-rich (a compensating indirect effect). For the intensive margin (full-day vs. half-day) we find more additional reductions in parenting activities, but these are compensated for by lower education mothers during non-center hours. Our findings represent novel evidence that activities in the home environment are a complement to center-based care, highlighting a credible additional mechanism for child development effects of centerbased care.
Keywords: D13; I21; J13; 330; Child care; Child development; Time use; Parenting investments; Oster method